Provide a Lean and Agile Strategy for an Antifragile Sustainable Supply Chain in the Construction Industry(residential complex) - Sadeghi, Soheil; Akbarpour, Abbas; Abbasianjahromi, Hamidreza (Cleaner Logistics and Supply Chain, 2022)
Supply chain management is one of the main approaches in the construction industry to deal with chaotic situations. Sanctions, corruption, Covid-19 pandemic, inflation, and other factors have created chaotic situations for Iranian companies. The main solution for companies is to formulate their supply chain strategies in line with their high-level goals. Lean and agile approaches are competitive strategies that, together with task strategies, can improve the performance of organizations in the medium and long term. In this study, the purpose is to provide the appropriate strategy among lean and agile strategies according to the performance of sustainable supply chain management in Didas Company. Its goal is to maintain and improve the competitive situation, and functional and environmental criteria of the company in order to deal with complexity and chaos when constructing residential complexes. The managers of Didas company who are familiar with the subject are the statistical population in this article. The snowball method was used to select individuals. By studying the articles, the criteria and performance indicators of the construction industry were extracted. Then, the Hierarchical Fuzzy Best-Worst Method (HF-BWM) was used to prioritize. Finally, lean, agile, lean-agile, and agile-lean strategy were ranked by Grey VIKOR method. The results of the first analysis show that economic performance with a weight of 0.4515 is placed in the first priority, operational social performance and environmental performance with a weight of 0.395 and 0.1533 are placed in the second and third priority, respectively. According to the results of the second analysis, the Agile-Lean strategy based on sustainable supply chain leadership strategy with a weight of 0.0219 is placed as the first priority. It is a suitable strategy to improve performance indicators in the supply chain of Didas company. Because this strategy has a high potential that might keep balance and improving the situation in the chaotic and unsustainable situations.